AN ANALYSIS OF COMMUNITY EMPOWERMENT IN BOOSTING THE COASTAL ECONOMY IN THE VILLAGE OF WIRINGTASI, PINRANG REGENCY - Andi Dian Islamiah; Parman, Parman; Fajar Ladung (DECISION : Jurnal Ekonomi dan Bisnis, 2026)
Coastal communities are social groups inhabiting transitional areas between land and sea, such as beaches, estuaries, and mangrove areas, whose livelihoods are primarily dependent on marine resources. This study aims to analyze the role of village officials in the coastal community empowerment process and the impact of economic empowerment on improving community welfare in Wiringtasi Village, Suppa District, Pinrang Regency. A qualitative method with a descriptive empirical approach was employed. Data were collected through field observations, in-depth interviews with village officials, community leaders, fishermen, and fish farmers, as well as documentation studies. Data analysis followed three stages: data reduction, data presentation, and conclusion drawing based on the Miles and Huberman (2014) model. The results indicate that the Wiringtasi Village Apparatus has carried out four empowerment roles: (1) sustainable natural resource management through sea turtle conservation and mangrove planting; (2) facilitation of access to economic resources, including digital marketing and entrepreneurship training; (3) community involvement in decision-making through village deliberations; and (4) ecological and environmental protection. The impact of this empowerment is reflected in increased community income, improved quality of life, strengthened social networks between fishermen, fish farmers, and local government, as well as the sustainable preservation of coastal ecosystems.